2007
DOI: 10.1007/s10585-007-9120-8
|View full text |Cite
|
Sign up to set email alerts
|

N-WASP is a putative tumour suppressor in breast cancer cells, in vitro and in vivo, and is associated with clinical outcome in patients with breast cancer

Abstract: N-WASP is a key regulator of cell migration and actin polymerisation. We examined the correlation of N-WASP, with human breast cancer, in vitro, in vivo and in clinical breast cancer tissue. Immunohistochemical study of frozen sectioned human breast mammary tissues (n=124) revealed that mammary epithelial cells stained positively for N-WASP and that cancer cells in tumour tissues stained very weakly. Quantitative RT-PCR revealed that breast cancer tissues had significantly lower levels of N-WASP compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 30 publications
5
57
0
Order By: Relevance
“…It has been reported that lower levels of expression of N-WASP in whole breast tumor tissue is correlated with poor outcome, using disease-free survival as the end point (Martin et al, 2008). However, this study did not evaluate the behavior of the migratory and disseminating population of breast cancer cells in the primary tumor or the requirement of N-WASP for these phenotypes in vivo.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…It has been reported that lower levels of expression of N-WASP in whole breast tumor tissue is correlated with poor outcome, using disease-free survival as the end point (Martin et al, 2008). However, this study did not evaluate the behavior of the migratory and disseminating population of breast cancer cells in the primary tumor or the requirement of N-WASP for these phenotypes in vivo.…”
Section: Discussionmentioning
confidence: 94%
“…A previous study has shown that the overexpression of N-WASP or DN N-WASP does not affect cell-cell junctions in epithelial cells (Yamaguchi et al, 2002) and that DN N-WASP overexpression had little effect on random cell migration in vitro, indicating that N-WASP is not involved in general cell locomotion. A different study (Martin et al, 2008) reported that N-WASP overexpression increased adhesiveness in breast cancer cells and reduced tumor growth rate.…”
Section: Discussionmentioning
confidence: 96%
“…Sections were counterstained in Mayer's haematoxylin for 1 min, dehydrated, cleared and mounted in DPX. Following this, the sections were analyzed for staining intensity as previously described (9,10).…”
Section: Methodsmentioning
confidence: 99%
“…It was recently revealed that an absence or decrease in WASP family protein expression in T cells has been associated with a decrease in cell proliferation (33). In contrast, N-WASP has been implicated as a tumor suppressor in breast epithe- lium (45). One can speculate that N-WASP, via its apparent effect on actin cytoskeleton dynamics, regulates keratinocyte adhesion to the extracellular matrix, a process known to control keratinocyte growth (37).…”
Section: N-wasp Regulates Keratinocyte Proliferation But Is Not Requmentioning
confidence: 99%